2022
DOI: 10.1039/d2fo00994c
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate alleviates galactose-induced aging impairment via gut–brain communication

Abstract: The study aimed to determine whether gut-brain communication could be modulated by Epigallocatechin-3-gallate (EGCG) in a mouse aging model that was established by daily injection of D-galactose (D-gal) for 10...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…A key observation of growth and development in mice is the change in body weight, while the degree of cellular senescence can be reflected by the organ index. Numerous studies have observed significant decreases in the organ indices of immune organs in aging mice [15]. In our study, the organ indices of mice in the model group were significantly lower than those of the other groups, and the organ indices of brain, liver and spleen in the dagliflozin intervention group showed significant increases compared to those of the senescent group.…”
Section: Discussioncontrasting
confidence: 38%
“…A key observation of growth and development in mice is the change in body weight, while the degree of cellular senescence can be reflected by the organ index. Numerous studies have observed significant decreases in the organ indices of immune organs in aging mice [15]. In our study, the organ indices of mice in the model group were significantly lower than those of the other groups, and the organ indices of brain, liver and spleen in the dagliflozin intervention group showed significant increases compared to those of the senescent group.…”
Section: Discussioncontrasting
confidence: 38%
“…When the gut homeostasis is compromised, anti-inflammatory molecules such as SCFAs are decreased and an imbalance occurs with levels of pro-inflammatory molecules (e.g., LPS or biofilm amyloid fibres) [97,98] resulting in greater permeability of the intestinal wall, increased mitochondrial ROS production, neuronal peroxisome proliferation, as well as neurotoxin aggregation and, potentially, neurodegeneration. The decline in free radicals in the brain, through the reduction of oxidation by the modulation of the gut microbiome with the consumption of (poly)phenolic compounds, is reflected by the decrease in the level of malondialdehyde (MDA) and ROS, which is concordant with the changes in SCFAs production or the increase in SCFA-producing bacteria in several studies [74,80,82,85,[99][100][101][102][103][104][105][106] (Table 1). This interplay between gut microbiota and brain oxidative stress highlights the potential of the gut microbiome to modulate the brain redox status.…”
Section: Insight Into Associated Molecular Mechanismsmentioning
confidence: 62%
“…This is notably illustrated by an a posteriori increase in neuroinflammation, which was observed following menopause and the associated fall in oestrogen levels [109,110]. In models of (neuro)inflammatory diseases, e.g., direct administration of amyloid beta Aβ1-42 peptide [111], D-galactose [68,[80][81][82]99,104,105] or by other neurotoxins [111], oxidative stress, inflammation and mitochondrial dysfunction occur, usually in parallel to an abnormal gut ecosystem. This is of major importance as it validates the bidirectionality of the gut-brain axis, with induced neuro-disorders causing deleterious changes at the level of the microbiome.…”
Section: Insight Into Associated Molecular Mechanismsmentioning
confidence: 99%
“…Taxifolin was reported to alleviate dextran sulfate sodium (DSS)-induced ulcerative colitis by acting on gut microbiome to produce butyric acid (Li et al, 2022). In addition, hesperetin-7-Oglucoside (Wu et al, 2021), rutin (Cheng et al, 2022), icariside I (Chen et al, 2021), quercetin (Liu et al, 2019a), epigallocatechin-3-gallate (Luo et al, 2022), epigallocatechin-3-gallate, and caffeine (Zhu et al, 2021) likewise showed similar effect. SCFAs maintain human health and may regulate some signaling pathways.…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 98%